Strategies for Strengthening Integrity and Anti-Corruption among Village Government Apparatus - Mahyudin (AIQU: Journal Multidiscipliner of Science, 2025)
The increase in village authority and budget through the Village Fund (DD) and Village Fund Allocation (ADD) has not been fully accompanied by the strengthening of integrity and adequate anti-corruption systems. This study aims to identify strategies to strengthen the integrity of village officials and prevent corruption by taking a case in Lapandewa Jaya Village, South Buton Regency. This research uses a descriptive qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and focus group discussions (FGDs), then analysed thematically. The results showed that the weak integrity of the village apparatus was caused by the dominance of decision-making, lack of transparency, and low community participation. The strategies for strengthening integrity found include: integrity value education, increasing transparency through information digitisation, community-based participatory supervision, and sanctions and rewards based on local social values. This research concludes that an integrative approach-combining regulative, cultural, and participatory-is a strategic step in building village governance with integrity and free from corruption.